2009
DOI: 10.1097/mat.0b013e3181ba133b
|View full text |Cite
|
Sign up to set email alerts
|

Organ Donation After Cardiac Determination of Death (DCD): A Swine Model

Abstract: Donors after Cardiac Death (DCD) may reduce the organ scarcity; however, their use is limited because of warm ischemia time. Fortunately, this is less important in a subclass of DCD called expected (e-DCD), those with irreversible but incomplete brain injury. This study analyzed hemodynamic/pulmonary data to establish a clinically relevant model of cardiac death that would simulate an e-DCD setting. Hemodynamics, pulmonary artery flows, arterial blood gasses, and left atrial pressure were recorded q 5 minutes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…There is room for experimental studies in these fields and particularly for large animal models. Several recent studies have shown that promising protocols could be used in the clinical situation [ 92 , 102 , 103 , 120 , 126 ]. More recently, new protocols have been evaluated and the use of normothermic venoarterial extracorporeal membrane oxygenation support seems an interesting alternative [ 80 ].…”
Section: Different Models For Renal Transplantation and Ischemia-rmentioning
confidence: 99%
“…There is room for experimental studies in these fields and particularly for large animal models. Several recent studies have shown that promising protocols could be used in the clinical situation [ 92 , 102 , 103 , 120 , 126 ]. More recently, new protocols have been evaluated and the use of normothermic venoarterial extracorporeal membrane oxygenation support seems an interesting alternative [ 80 ].…”
Section: Different Models For Renal Transplantation and Ischemia-rmentioning
confidence: 99%
“…We have studied many of the details of E-DCDD in the laboratory, using a porcine model of apneic CA (21,22). We have learned that heparin given 5 min after CA is as effective as heparin given before; that the perfusion temperatures can be allowed to gradually drop from 37-C to room temperature, obviating the need for a heat exchanger and water bath in the circuit (23); that kidneys and livers can be successfully resuscitated by ECS after more than 30 min of warm ischemic time; and that lungs can be successfully resuscitated by ECS (relying on bronchial flow from the distal aorta) and lung function can be evaluated despite the fact that there is no pulmonary circulation (24).…”
Section: Discussionmentioning
confidence: 99%
“…In the previous literature, several animal models are described focusing on different DCD protocols. However, none of these studies has included brain death diagnosis [44–46].…”
Section: Discussionmentioning
confidence: 99%